Re-articulation in Zora Neale Hurston’s Their Eyes Were Watching God - Sharma, Divya (The Grove - Working Papers on English Studies, 2023)
Zora Neale Hurston’s most acclaimed novel, Their Eyes Were Watching God (1937), juxtaposes the sensuous side of ecology with that of female sexuality and sensuousness, through the epiphany of the blossoming pear tree. The present research article explores this idea to establish Zora Neale Hurston as a womanist who anticipates ecofeminism and ecosexuality creating a female protagonist who finds a voice narrating her story.